Pola Relasi Gender dan Kehidupan Sosial Ekonomi dalam Keluarga Buruh Perempuan di Jember (Studi Kasus pada Buruh Perempuan di Desa Panti Jember): Gender Relations Patterns and Socio-Economic Life in Female Laborer Families in Jember (A Case Study of Female Laborers in Panti Village, Jember) - Dwi Puspitarini (Fenomena, 2011)
In general discourse, it is impossible to discuss "gender" without addressing the features of man-woman relations. The enthusiasm for such discussions has grown alongside increasing public awareness of gender relations. In earlier periods, men held a higher position in society than women. This condition was reflected in all aspects of life, including the economic sphere. Gender ideology and patriarchal culture have resulted in gender inequality, particularly in the occupational domain, as evidenced by the male-dominated Workforce Participation Rate. Several factors contribute to this inequality, including the marginalization of women in both public and domestic spheres. The subordination of women in social and cultural aspects also leads to discrimination. Stereotyping and lower education levels further limit women's work participation. Consequently, many women opt for informal sector jobs, which offer very low wages and lack health, legal, and financial security. Dalam wacana umum, tidak mungkin membahas "gender" tanpa menyertakan ciri-ciri relasi antara laki-laki dan perempuan. Semangat diskusi meningkat seiring dengan kesadaran masyarakat akan relasi gender. Pada masa sebelumnya, posisi laki-laki dalam masyarakat lebih tinggi daripada perempuan. Kondisi ini juga diterapkan dalam segala aspek kehidupan, termasuk aspek ekonomi. Ideologi gender dan budaya patriarki telah menimbulkan ketimpangan gender, terutama di bidang pekerjaan. Hal ini terlihat dari tingkat Partisipasi Angkatan Kerja yang didominasi oleh laki-laki. Beberapa faktor memengaruhi ketimpangan tersebut, termasuk marginalisasi perempuan di ranah publik maupun domestik. Subordinasi perempuan dalam aspek sosial atau budaya juga berdampak pada diskriminasi. Pelabelan (stereotip) terhadap perempuan dan tingkat pendidikan yang rendah turut memengaruhi partisipasi perempuan dalam pekerjaan. Akibatnya, banyak perempuan memilih bekerja di sektor informal dengan upah rendah dan tanpa jaminan kesehatan, hukum, maupun keuangan.